2014
DOI: 10.1063/1.4898322
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability and depolarization of manganese-doped (Bi0.5Na0.5)1−xBaxTiO3 relaxor ferroelectrics

Abstract: This work reveals that 0.5 mol. % manganese (Mn) doping in (Bi0.5Na0.5)1−xBaxTiO3 (x = 0 and 0.075) solid solutions can increase structural thermal stability, depolarization temperature (Td), piezoelectric coefficient (d33), and electromechanical coupling factor (kt). High-resolution X-ray diffraction and transmission electron microscopy reveal coexistence of rhombohedral (R) R3c and tetragonal (T) P4bm phases in (Bi0.5Na0.5)0.925Ba0.075TiO3 (BN7.5BT) and 0.5 mol. % Mn-doped BN7.5BT (BN7.5BT-0.5Mn). (Bi0.5Na0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…There are several methods to determine the T d in the literatures, whereas for the same material the T d value obtained through different measuring methods have a correlation but apparent disparity up to 30°C . The TSDC is a highly recommendable method for T d measurement with technically viable necessitating furnace and electrometer .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods to determine the T d in the literatures, whereas for the same material the T d value obtained through different measuring methods have a correlation but apparent disparity up to 30°C . The TSDC is a highly recommendable method for T d measurement with technically viable necessitating furnace and electrometer .…”
Section: Resultsmentioning
confidence: 99%
“…, reported that the composite of 0.94BNT–0.06BT and ZnO possessed excellent piezoelectric properties as well as elevated temperature stability . Studies also suggested that Mn doping in BNT and 0.925BNT–0.075BT ceramics improved electrical properties and thermal stability . Zhu et al.…”
Section: Introductionmentioning
confidence: 98%
“…A little lattice mismatch between PLCT and NKBT makes the peak splitting on (100) and (200). All the samples show broadened (200) peaks, which can be assumed a variety of ferroelectric phases indicating that this film may be close to the morphotropic phase boundary (MPB) [17]. Benefiting from the MPB effect, superior piezoelectric performance can be expected [18].…”
Section: Introductionmentioning
confidence: 98%
“…Generally, nano-sized BaTiO 3 -based powder is usually prepared via wet chemical method such as the precipitation method [5,6], the sol-gel press [7], and traditional solid-state method [8][9][10][11][12]. In general, a traditional solid-state method is used to prepare MLCCs ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…The core is doped with some elements to increasing the Curie point so that achieving better temperature stability. Among such dopants, the bismuth has a signifi cant effect on the fabrication of MLCCs [19,20].…”
Section: Introductionmentioning
confidence: 99%